WHAT EXTERNAL FACTORS DETERMINE ONLINE LEARNING DIFFICULTIES ON JUNIOR HIGHSCHOOL STUDENTS? - Angie Wando; Andrew Christian Aseng; Lanemey Brigitha Pandeirot (Sean Institute, 2023)
This research was conducted to find out what are the external factors that cause online learning difficulties in learning social studies subject at SMP UNKLAB Airmadidi during pandemic. This research is an aquantitative descriptive research. Respondents in this study were students of class VIII SMP UNKLAB Airmadidi with 90 students filling out the questionnaire. Data collection was carried out directly in each class using a questionnaire. This study finds that there are several external factors that cause online learning difficulties which have a fairly high level of difficulty, namely family factor, internet access and its cost factor, environmental factor, and school factor. Meanwhile, the technical skill factor has a low level of difficulty, meaning that students do not find it difficult in terms of technical skills.